Realization of optimum mode of movement of roller forming installation on acceleration of fourth order - Loveykin, V. S.; Pochka, K. I. (НУБіП України, 2018)
For the purpose of increase in reliability and durability of roller forming installation the optimum mode of back and forth motion of the forming cart on acceleration of the fourth order is calculated. Kinematic characteristics of the forming cart at the optimum mode of the movement on acceleration of the fourth order are calculated. The design of roller forming installation with the drive from the high-moment step engine which is built in the rolling rollers of the forming cart is offered and provides the optimum mode of back and forth motion of the forming cart on acceleration of the fourth order. Use in installation of the specified driving mechanism leads to improvement of quality of a surface to the processed concrete mix, reduction of dynamic loadings in elements of the driving mechanism, to disappearance of excess destructive loads of a frame design and, respectively, to increase in reliability and durability of installation in general.
Реалізація оптимального режиму руху ролика формуючої установки на прискорення четвертого порядку
В цілях збільшення надійності і довговічності ролика формуючи встановлення оптимального режиму руху вперед і назад в формуючої візки на розгін четвертого порядку розраховується. Кінематичні характеристики формуючи кошик при оптимальному режимі руху на прискорення четвертого порядку розраховуються. Дизайн роликові формувальні установки з приводом від високого моменту крокового двигуна, який побудований на прокатних роликів, утворюють візок і забезпечує оптимальний режим руху вперед і назад формуючої візки на розгін четвертого порядку. Використання в установці зазначеного приводного механізму призводить до покращення якості оброблюваної поверхні бетонної суміші, зниження динамічних навантажень в елементах приводного механізму, до зникнення зайвого руйнівних навантажень конструкція рами і, відповідно, збільшити надійність і довговічність установки в цілому.
Keywords: roller forming installation; mode of the movement; step engine; drive; режим руху; крок двигуна; привод; роликові формувальні установки